2007
DOI: 10.1016/j.epsl.2007.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Soluble and insoluble lithium dust in the EPICA DomeC ice core—Implications for changes of the East Antarctic dust provenance during the recent glacial–interglacial transition

Abstract: Continental dust impurities in Antarctic ice provide information on climate changes in the dust source areas and on past atmospheric circulation. We investigated records of dust species from the last 45 ka in the East Antarctic EPICA DomeC (EDC) ice core with special emphasis on the lithium (Li) content of dust. We obtained two complementary Li-records using a new Ion Chromatography (IC) technique in line with Inductively Coupled Plasma-Sector Field Mass Spectroscopy (ICP-SFMS). Concentrations of soluble Li (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
5
20
1
Order By: Relevance
“…Ce an shows marked glacial/interglacial variation that may indicate contributions of aeolian dust from different sources during different climatic periods, as suggested by previous work (Delmonte et al, 2004a;Siggaard-Andersen et al, 2007;Ruth et al, 2008). A large variation in Ce an Distance above Lake Vostok (m) appears in AC 1 where we can observe the maximum Ce an (1.33) and the most negative Ce an (0.76), similar to typical Ce an found in saline marine waters (Alibo and Nozaki, 1999).…”
Section: Ce Anomalysupporting
confidence: 85%
“…Ce an shows marked glacial/interglacial variation that may indicate contributions of aeolian dust from different sources during different climatic periods, as suggested by previous work (Delmonte et al, 2004a;Siggaard-Andersen et al, 2007;Ruth et al, 2008). A large variation in Ce an Distance above Lake Vostok (m) appears in AC 1 where we can observe the maximum Ce an (1.33) and the most negative Ce an (0.76), similar to typical Ce an found in saline marine waters (Alibo and Nozaki, 1999).…”
Section: Ce Anomalysupporting
confidence: 85%
“…Grousset and Biscaye 2005). More recently, new isotopic and elemental composition systems (e.g., Pb, Li, He isotopes) have been utilized to fingerprint geochemically the dust (Vallelonga et al 2010;Gabrielli et al 2010;Marino et al 2008;Winckler and Fischer 2006;Siggaard-Andersen et al 2007); yet, geochemical data There is increasing consensus that dust deposited in Antarctica during interglacial time periods is derived from a mixture of dust sources rather than a single source. Potential sources include different regions within southern South America and other sources like AUS (Revel-Rolland et al 2006;Delmonte et al 2007) or possibly the PunaAltiplano area (Delmonte et al 2008a;Gaiero 2008), and match the limited data on the isotopic signature of interglacial dust from the studied ice cores.…”
Section: Comparing Model Results With Observations: Current Climatementioning
confidence: 99%
“…Previous studies on the mineralogy of EDC dust have identified that the dominant dust source area was Patagonia during the LGM and that multiple dust sources including Australia may have contributed after ~16 kyr BP (Delmonte, Basile‐Doelsch, et al, ; Delmonte et al, ; Gili et al, ; Marino et al, ; Revel‐Rolland et al, ; Siggaard‐Andersen et al, ; Vallelonga et al, ; Wegner et al, ). Atmospheric model simulations have suggested that Patagonian dust is transported via the lower troposphere, while Australian dust is transported via the middle to upper troposphere (Krinner et al, ; Li et al, ).…”
Section: Discussionmentioning
confidence: 99%